Global and local factors behind the authigenesis of Fe-silicates (Glauconite/Chamosite) in Miocene strata of Northern Tunisia. (December 2021) - Tounekti, Abdelbasset; Boukhalfa, Kamel; Choudhury, Tathagata Roy; Soussi, Mohamed; Banerjee, Santanu
Abstract: The exceptionally glauconite-rich Miocene strata, superbly exposed throughout the front of the nappes zone of northern Tunisia, show marked contrast in Fe-silicate authigenesis within and outside foraminifera chambers. Glauconite forms by the alteration of fecal pellet, quartz, feldspar, volcaniclastic particles, feldspar, and quartz. X-ray diffraction patterns show the characteristic peaks of the 'evolved' variety glauconite. The glauconite contains high K2 O and Al2 O3 and moderate to high Fe2 O3 (total). While chamosite occurs solely as infillings within bioclasts pores, containing high Fe2 O3 and Al2 O3 . Each of the glauconitic intervals coincide with the peak rise of third order sea-level cycles during the Burdigalian-Langhian time. Glauconite occurs at the base of coarsening- and thickening-upward hemicycles consisting of shale and sandstone, recording a shallowing upward trend across offshore-shoreface settings. The glauconitic parasequences are correlated across the Tethyan margin. Within the Miocene succession of Tunisia, glauconite formed on shallow marine dysoxic bottom water condition charged with abundant cations. On the other hand, anoxic micro-environment within the bioclasts pore spaces, induced by the decomposition of organic matter, favored the fixation of Fe 2+ into the crystal structure, forming chamosite. Contemporaneous volcanism in Algeria and surrounding areas, in response to the African-European plate convergence, appears to be the most significant sources of Fe and other cations necessary for green clay authigenesis. Therefore, the occurrence of glauconite in the Miocene succession of Tunisia, is influenced by the combination of eustacy and volcanism, the type of substrate dictating the ultimate composition of the authigenic Fe-silicates. Highlights: Authigenic Fe-silicates including glauconite and chamosite form abundantly in low-energy, offshore sediments of Miocene Bejaoua facies. While glauconite forms by the alteration of pellets, quartz, feldspar and volcaniclastics, chamosite occupies exclusively the pores within bioclasts.